The Influence of Product Innovation, Brand Image, and Brand Trust on The Purchasing Decisions (Studi Literature) - Huiser Mangalindung, Giovani; Hendayana, Yayan (Dinasti Publisher, 2024)
The research objective is to determine the effect of product innovation, brand image, and brand trust on purchasing decisions. The problem studied is the intense competition between product in Indonesia. This research study uses the qualitative based on literature and library research approaches. Theoretical and historical analyses are used to understand purchasing decisions. Product innovation, brand image, and brand trust play and important role in purchasing decisions. This study also describes theoretical measurement elements for future research to describe, explain, and measure purchase decision based on theoretical research.